Toxicological analysis of metabolites in ischemic stroke based on salivary metabolomics - Liu, Yan-Song; Long, Yu-Yan; Liu, Jie; Liu, Yu-Chen; Zhang, Shuang; Xu, Yi-Jia; Fu, Shu-Yue; Li, Hua; Liu, Wang-Hua (Frontiers in Molecular Biosciences, 2025)
ObjectiveTo elucidate the characteristic patterns of salivary metabolic network instability in IS patients, reveal the association mechanism between amino acid-lipid-nucleotide metabolic cascade imbalance and stroke progression, and provide experimental basis and translational pathway for the development of diagnostic and therapeutic strategies based on metabolic microenvironment regulation.MethodsThis study focused on salivary metabolomics. A prospective cohort design (40 IS patients and 30 healthy controls) was combined with high-resolution liquid chromatography-mass spectrometry (LC-MS/MS) to systematically analyze the molecular characteristics and toxicological mechanisms of metabolic disorders in stroke. Orthogonal partial least squares discriminant analysis (OPLS-DA) and game theory feature weighting method were used to screen differential metabolites, and toxicity evaluation was performed by integrating ADMETlab and ProTox databases. Finally, molecular docking technology was used to verify the metabolite-target interaction network.ResultsA total of 488 salivary metabolites were identified, of which 167 showed significant differences between groups, including 4.3-fold increase in arginine, 3.5-fold increase in xanthine, and 2.1-fold increase in lipoxin A4. Toxicity prediction showed that xanthine has potential neurotoxicity and blood-brain barrier penetration ability (BBB = 0.90). Its molecular docking with targets such as XDH and PNP showed stable binding energy, suggesting that it participates in the pathological process of stroke by regulating purine metabolism and oxidative stress.ConclusionA panoramic analysis framework of salivary metabolomics in ischemic stroke was constructed, and the cascade disorder of the amino acid-lipid-nucleotide metabolic network was elucidated. The screened core metabolite markers and their regulatory pathways not only provide highly specific tools for early diagnosis of stroke, but also provide research basis for the development of innovative therapies based on metabolic microenvironment regulation.